Pendidikan Islam: Konsep, Masalah, dan Solusi - Jaohar Tsani, Muhammad; Sauri, Sofyan (Universitas Hamzanwadi, 2024)
Islamic education is a process of guiding and developing students to achieve maturity by Islamic principles. The goal is to instill holiness, morals, and truth to shape individuals with personality and noble character. The concept of Islamic education includes tarbiyah, ta'lim, and ta'dib. Tarbiyah involves the development of children's potential; ta'lim focuses on the transfer of knowledge, while ta'dib emphasizes the formation of character and morals. The objectives of Islamic education include obedience to Allah, the formation of good character, and the development of skills. The Qur'an provides a relevant teaching foundation for education, such as the story of Luqman and his five education principles. Problems in education often involve a lack of understanding of the role and purpose of Islamic education. The solutions include introducing faith from an early age, improving parental upbringing patterns, and introducing character education at an early age. This aims to strengthen the emotional intelligence of children and shape positive character